Tensile Strength of Carbon Fiber/Epoxy Composite Manufactured by the Bladder Compression Molding Method at Variable Curing Temperatures - Antonius Dwi Setyoko; Gesang Nugroho (Departmen Teknik Mesin dan Industri, Fakultas Teknik, Universitas Gadjah Mada, 2020)
Corrosion-resistant, high-strength, low-density composite materials are seeing increased applications in a wide variety of products. The composite constituents of matrix and reinforcement require molding technologies and methods to generate products. The bladder compression molding method is an effective method of manufacturing of composite products with a tubular shape, cavity, and/or closed contour. The properties of the composite materials produced are determined by three variables, namely. curing pressure, temperature, and time. This research was conducted to learn the effect of temperature on the mechanical properties of the composite materials produced from the process with the bladder compression molding method. Based on the thickness, tensile strength, and modulus of elasticity of the product from the experiment conducted, the optimal temperature of the process was found to be 120 ºC